Optimalisasi Patroli Dialogis Unit Turjawali Satuan Sabhara dalam Mencegah Tindak Pidana Curanmor - Indarsari, Andi Anisa (Advances in Police Science Research Journal, 2019)
This research is motivated by the high number of criminal acts of curanmor in the Bogor police jurisdiction which then causes unrest in the community. The lack of optimal efforts to prevent criminal acts of fraud committed by the Sabhara unit turjawali unit through dialogical patrol will be discussed in this study. The aim is to be able to describe the implementation of the Dialog patrol of the Sabhara unit in the Sabhara unit in preventing criminal acts of fraud in the Bogor police jurisdiction. In this study, the theory used by researchers is based on law enforcement, management theory, and AIDDA communication theory. The concept used by researchers is based on the concept of optimization, the concept of dialogical patrol, the concept of crime prevention, and the concept of fraud. The research method uses a qualitative approach whose results are strengthened by the findings of observations, document studies, and interviews with information sources. The technique used for data analysis is data reduction, data presentation, and concluding. This research also applies empirical techniques using methods and techniques in the field. The results of this research found that the dialogical patrol of the turjawali unit in preventing criminal acts of curanmor was still not optimal because there were still shortages at each stage of the activity as well as the knowledge of the patrol officers. Factors that influence the implementation of dialogical patrols are human factors, budget factors, facilities and infrastructure factors, method factors, and target factors. Based on the results of the study, researchers suggest improving facilities and infrastructure, developing the ability of patrol members, especially in communication science, and increasing public awareness to be able to participate with the police in preventing criminal acts of fraud.